Remaking Central Europe the League of Nations and the former Habsburg lands (The history and theory of international law, 2020)
Over the last two decades, the "new international order" of 1919 has grown into an expansive new area of research across multiple disciplines. With the League of Nations at its heart, the interwar settlement's innovations in international organizations, international law, and many other areas shaped the world we know today.This book presents the first study of the relationship between this new international order and the new regional order in Central and Eastern Europe after the collapse of the Habsburg empire. An analysis of the co-implication of these two orders is grounded in four key scholarly interventions: understanding the legacies of empire in international organizations; examining regionalism in the work of interwar international institutions; creating an integrated history of the interwar order inEurope; and testing recent claims of the conceptual connection between nationalism and internationalism.With chapters covering international health, international financial oversight, human trafficking, minority rights, scientific networks, technical expertise, passports, commercial treaties, borders and citizenship, and international policing, this book pioneers a regional approach to international order, and explores the origins of today's global governance in the wake of imperial collapse